Learning Styles Of Postgraduate And Undergraduate Healthcare Management Students Of Tehran University Of Medical Sciences - Zhila Najafpoor; Faezeh Tajfar; Mandana Shirazi; Fatemeh Keshmiri (Tehran University of Medical Sciences, 2014)
Background and Aim: Learning styles are among efficient factors in the teaching-learning process. The aim of the present study was to assess healthcare management students' learning styles at Tehran University of Medical Sciences (TUMS). Materials and Methods: This descriptive cross-sectional study was conducted on healthcare management students selected randomly through stratified sampling (response rate = 85%). The data collection tool used in this study was Kolb learning style questionnaire (Cronbach Alpha was 0.7-0.9). The data were analyzed through descriptive and analytical tests (χ2 and t-test). Results: Most postgraduate students preferred the Accommodate Style (55.6% of PhD students and 64% of MCs students). The majority of undergraduate students, however, preferred the Convergent Style (45.67%). Conclusion: As to these students' dominant learning styles, the results of the study emphasized the use of "teaching methods based on Role Playing and Simulation" among postgraduate students and "Problem-Based Learning" among undergraduate students.